Psychiatric Diagnosis Among Patients With Self-Harm Attempts In A Tertiary Care Centre (Journal of Psychiatrists' Association of Nepal, 2021)
Introduction: Self harm or suicidal attempt is one of the most common primary psychiatric emergencies. It has been increasing daily but unfortunately people seeking attention and help from psychiatrist is still lagging. This study aims to observe psychiatric comorbidities among self-harm or suicidal attempt.Material And Method: Those patients who presented with suicidal attempts and related problems in Nobel Medical College Teaching hospital, Biratnagar were assessed for socio demographic and clinical variables. Convenience sampling method was used. MINI 6.0 was applied to all the patients to see for psychiatric disorders. Those who had positive psychiatric disorders in MINI 6.0 were then reassessed according to ICD-10 (International classification of diseases, clinical description and diagnostic guidelines) and final psychiatric disorder was considered. Becks’ suicide intent scale was used to assess the intensity of suicide. Data entry was done using Microsoft Excel and statistical analysis was done by using IBM SPSS Version 16.0.Results: The result showed that 56.17% of the participants had some form of psychiatric comorbidities. The commonest among them was depression (23.97%), adjustment disorder (21.9%), followed by alcohol use disorder (5.47%) and others. The most common method of suicidal attempt was by poisoning (86.3%), followed by hanging (7.5%) and self- inflicted cut injury (6.2%). Psychosocial stressors were present in 84.9% of patients and 15.1% did not have notable psychosocial stressors.Conclusion: Patients with self-harm or suicidal attempt have common psychiatric comorbidities depression and adjustment disorder being the most prevalent entities. Hence, every suicidal attempt becomes common psychiatric emergency condition in Nepal.